2003
DOI: 10.1001/archpsyc.60.6.585
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Structural Brain Abnormalities and Their Relationship to Clinical Outcome

Abstract: There are ongoing changes in the brains of schizophrenic patients during the initial years after diagnosis despite ongoing antipsychotic drug treatment. These progressive changes seem to be most evident in the frontal lobes and to correlate with functional impairment. Disruptions in neurodevelopment or neural plasticity may act alone or in combination to bring about these progressive brain deficits in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
289
0
18

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 504 publications
(328 citation statements)
references
References 74 publications
21
289
0
18
Order By: Relevance
“…For example, Ettinger et al (2004) showed that, although no volumetric differences were found between patient and control groups, different brain region volumes related differently to antisaccadic eye movements between the groups; suggesting abnormal structure-function relationships within the patient group. In addition, a plethora of research has found specific structural abnormalities to be associated with the cognitive/behavioral diagnostic criteria for schizophrenia, which are not found in healthy controls (e.g., Ho et al, 2003;Szeszko et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ettinger et al (2004) showed that, although no volumetric differences were found between patient and control groups, different brain region volumes related differently to antisaccadic eye movements between the groups; suggesting abnormal structure-function relationships within the patient group. In addition, a plethora of research has found specific structural abnormalities to be associated with the cognitive/behavioral diagnostic criteria for schizophrenia, which are not found in healthy controls (e.g., Ho et al, 2003;Szeszko et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum also has been implicated in psychiatric disorders including schizophrenia (Andreasen, Paradiso and O'Leary, 1998;Andreasen, 1999), bipolar disorder (Lauterbach, 1996), and autism (Carper and Courchesne, 2000). In schizophrenia abnormalities in the cerebellar node of the cortico-cerebellar-thalamic-cortical (CCTC) circuit are indicated by both structural and functional findings (e.g., Stephan et al, 2001;Ho et al, 2003;Keller et al, 2003). Furthermore, cognitive disturbances associated with neurologic lesions affecting the cerebellum are similar to cognitive deficits reported in schizophrenia, including executive functioning deficits (Gimenez, et al, 2003) and affective deficits (Earnst and Kring, 1997) (c.f., Schmahmann and Sherman,1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, treatment approaches which can help to minimize antipsychotic medication or even administer them only selectively are of increasing importance. [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39]. Eine Studie wurde dreifach [30,31,32], eine weitere Studie doppelt publiziert [33,34].…”
Section: Frontal Brain Volume Reduction Due To Antipsychotic Drugs? Smentioning
confidence: 99%
“…Zwei Studien finden keine solche Korrelation [26,36]. Ho et al [36] In einer weiteren Studie, in der Patienten mittels SGA behandelt wurden, zeigte sich eine Korrelation zwischen der täg-lichen Antipsychotikadosis und der frontalen und sonstigen kortikalen grauen Substanz lediglich, wenn nicht für multiples Testen nach Bonferroni korrigiert wurde [33]. Mehrfach Erkrankte, Behandlung mit Antipsychotika der 1.…”
Section: Introductionunclassified